Profile of critical thinking skills of SMPN 37 Semarang students in learning science material on the human respiratory system - Salsabilla Zahirotul Maghfiroh; Ipah Budi Minarti; Eko Retno Mulyaningrum; Jamali Jamali (Institute of Computer Science (IOCS), 2023)
Students' critical thinking skills are one of the competencies that must be trained in the 21st century. Through this competency, students are expected to be able to be rational, not only in science learning but also in solving problems. This study aims to obtain a description of the critical thinking skills of students in each aspect of critical thinking skills in human respiratory system material. This research method is descriptive quantitative. This research aims to provide an accurate description of the characteristics of a situation or a phenomenon. This research used random sampling technique. This research instrument is in the form of HOTS-based Daily Test essay questions on human respiratory system material adapted to the Problem Based Learning model. The data of the research was taken from the results of students' answers are analyzed using a rubric that is adjusted to the aspects of critical thinking skills indicators. Based on the results of this research, the average percentage of critical thinking skills is 56.59% which is classified in the low category. The highest percentage is the interpretation aspect, the result is 68.80%, categorized as moderate. The lowest percentage is the inference. The result is 33.35% and classified as very low.